Kesenjangan Upah Gender Sektor Informal di Indonesia - Joan Marta; Rivatul Aini (Universitas Negeri Padang, 2025)
Wages for workers in the informal sector are generally lower than those in the formal sector, and the gender wage gap exacerbates this condition. This quantitative study analyzes the gender wage gap in Indonesia’s informal sector using variables such as education, work experience, training, region of residence, marital status, and gender as a moderating factor. Data from the 2020 National Labor Force Survey (SAKERNAS) were analyzed using Ordinary Least Squares (OLS) regression, robust regression, and the Blinder–Oaxaca decomposition. The results show that all variables have a significant effect on wages, while the Blinder–Oaxaca analysis reveals that the gap primarily stems from unexplained factors, which reflect gender discrimination. This study emphasizes the need for policies to improve access to education, training, and protection for female workers to reduce the gender wage gap in the informal sector.